Effect of Educational Intervention Program on Self-Efficacy of Individuals with Type 2 Diabetes Mellitus in South-East, Nigeria. - Okafor, Christiana Nkiru; Onyenekwe, Chinedu Charles; Okonkwo, Uchenna Prosper; Umunnah, Joseph Onuuwa; Okoro, Chukwuemeka Chukwubuikem; Mbanuzuru, Ahaoma Victor; Agunwah, Ukamaka Elizabeth; Odira, Chika Chioma; Makata, Eucharia Ngozi; Nwankwo, Chinenye Mercy (Kabale University, 2024)
Objectives: Diabetes Mellitus is a chronic disease, which requires a level of confidence among the sufferers in its management. This study investigated the effect of an educational intervention program on self-efficacy (SE) in diabetic individuals with type 2 diabetes mellitus in South-East, Nigeria. Methods: The study was a quasi-experimental controlled study, comprising 382 individuals with type 2 DM selected, and assigned to intervention (IG) and control groups (CG). The instrument for data collection was the Stanford Chronic Disease Self-Efficacy Scale (SCDS). Pretest data were collected, and thereafter education on diabetes management was given to the IG group. The IG was followed up for 6 months. At the end of 6 months, post-test data were collected using the same instrument. Data were analyzed using Pearson Chi-square test statistics. A P-value less than .05 alpha level was considered significant. Results: There was no statistically significant difference between the two groups before intervention. However, after 6 months of intervention, a significant proportion of participants’ scores in IG moved from low to either moderate or high SE in almost all the SE domains (P < .05. Conclusions: There was an improvement in most domains of self-efficacy in the intervention group after 6 months of educational intervention.